Flexicurity: Implications for Lifelong Career Guidance / Concept note commissioned by ELGPN - Sultana Ronald G (European Lifelong Guidance Policy Network, 2012)
This concept note outlines the concept, examines why it is increasingly attractive to policy-makers across Europe, and explores some of the issues and debates related to the concepts. What is flexicurity, Why is flexicurity increasingly attractive to policy makers across Europe, What are some of the issues and debates around flexicurity, What are the policy implications of flexicurity for career guidance, Bibliography.